The spreading of eostrogillidosis of Gobiidae family in Kremenchuk reservoir - Михайлютенко, С. М. (Scientific Progress & Innovations, 2017)
Based on the results of the studies, a significant spread of eustrongylidosis of Gobiidae family bulls was established in the conditions of the Kremenchuk reservoir. The larvae of the nematode had a filiform shape, a red color (sometimes areas of light pink color turned into a cherry blossom), a length of 35–53 mm, a width of 0.4–0.6 mm. Parasites were located mainly in the body cavity on the surface of the liver and intestine. The larvae were unencapsulated. It was found out that the EI was 37,25 % at an invasiveness rate of 1–4 ex./fish.